2020
DOI: 10.1093/jjco/hyaa168
|View full text |Cite
|
Sign up to set email alerts
|

Significance of prophylactic urethrectomy at the time of radical cystectomy for bladder cancer

Abstract: Background Prophylactic urethrectomy at the time of radical cystectomy is frequently recommended for patients with bladder cancer at a high risk of urethral recurrence without definitive evidence. The present study attempted to clarify the survival benefits of performing prophylactic urethrectomy. Methods We identified 214 male patients who were treated by radical cystectomy with an incontinent urinary diversion in our seven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Our analyses indicated improved PFS after urethrectomy at the time of RC in patients at high risk for UR. Similarly, Hakozaki et al reported the survival benefit of prophylactic urethrectomy in patients at high UR risk (multiple tumors and/or concomitant CIS) [ 7 ]. Interestingly, that survival benefit was also found in patients who did not receive neoadjuvant chemotherapy (NAC) [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our analyses indicated improved PFS after urethrectomy at the time of RC in patients at high risk for UR. Similarly, Hakozaki et al reported the survival benefit of prophylactic urethrectomy in patients at high UR risk (multiple tumors and/or concomitant CIS) [ 7 ]. Interestingly, that survival benefit was also found in patients who did not receive neoadjuvant chemotherapy (NAC) [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Hakozaki et al reported the survival benefit of prophylactic urethrectomy in patients at high UR risk (multiple tumors and/or concomitant CIS) [ 7 ]. Interestingly, that survival benefit was also found in patients who did not receive neoadjuvant chemotherapy (NAC) [ 7 ]. It can be hypothesized that patients at high risk for UR are more likely to benefit from NAC for downstaging and improving oncological outcomes, especially in those planned to spare urethra (e.g., ONB diversion).…”
Section: Discussionmentioning
confidence: 99%
“…5 Furthermore, it was reported that prophylactic urethrectomy at the time of RC might offer a survival benefit in patients with multiple tumors and/or concomitant carcinoma in situ, particularly those who do not receive neoadjuvant chemotherapy. 6 Therefore, performing prophylactic urethrectomy at the time of RC might be recommended for patients with multiple tumors and/or concomitant carcinoma in situ, prostatic involvement, previous history of non-MIBC, and positive frozen sections of the urethral margin. 5,6 The European Association of Urology and the National Comprehensive Cancer Network guidelines do not address prophylactic urethrectomy during RC when the creation of a neobladder is not being considered for urinary diversion in detail.…”
Section: Discussionmentioning
confidence: 99%
“…Hakozaki et al. [ 4 ] found that prophylactic urethrectomy was the only independent predictor of overall survival in patients with multiple bladder tumours and/or concomitant carcinoma in situ that were treated without neoadjuvant chemotherapy. Van Poppel and Thuer [ 8 ] recommended the use of prostatic urethral involvement in men and bladder neck involvement in women as the only indication for prophylactic urethrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Prophylactic urethrectomy at time of radical cystectomy is debatable and not routinely done by most urologic oncologists. A recent study (2021) found a survival benefit for prophylactic nephrectomy to patients that had multiple bladder tumours or concomitant carcinoma in situ at time of the transurethral resection [ 4 ]. Older studies found no significant survival benefits for prophylactic urethrectomy [ 5 ].…”
Section: Introductionmentioning
confidence: 99%